2012
DOI: 10.7589/2012-02-050
|View full text |Cite
|
Sign up to set email alerts
|

Host-Parasite Relationships During a Biologic Invasion: 75 Years Postinvasion, Cane Toads and Sympatric Australian Frogs Retain Separate Lungworm Faunas

Abstract: ABSTRACT:Invasive species may carry with them parasites from their native range, differing from parasite taxa found in the invaded range. Host switching by parasites (either from the invader to native fauna or from native fauna to the invader) may have important consequences for the viability of either type of host (e.g., their survivorship, fecundity, dispersal ability, or geographic distribution). Rhabdias pseudosphaerocephala (Nematoda) is a common parasite of cane toads (Rhinella marina) in the toad's nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Surveys of parasites and diseases in Australian cane toads provide some indication of the pathogen pressure faced by invading toads. At least one of the 100 toads brought to Australia from Hawaii in 1935 harbored a nematode lungworm native to South America [49] and this parasite is now common in Australian toad populations [50], though it lags behind the frontline of the toad invasion, where host density is too low for transmission [35]. Aside from harboring and outrunning a lungworm with which they have a long association, toads in Australia are also exposed to and can become infected with a suite of native pathogens [51][53], including pentastomids [37], myxosporea [54], and native nematode lungworms (GPB unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of parasites and diseases in Australian cane toads provide some indication of the pathogen pressure faced by invading toads. At least one of the 100 toads brought to Australia from Hawaii in 1935 harbored a nematode lungworm native to South America [49] and this parasite is now common in Australian toad populations [50], though it lags behind the frontline of the toad invasion, where host density is too low for transmission [35]. Aside from harboring and outrunning a lungworm with which they have a long association, toads in Australia are also exposed to and can become infected with a suite of native pathogens [51][53], including pentastomids [37], myxosporea [54], and native nematode lungworms (GPB unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Toads have invaded the region occupied by Litoria splendida only within the last three years, and examination of 31 Green Treefrogs collected over that period showed no parasitism by toad lungworms [18]. Dissections of seven L. caerulea at two sites where toads have been present for 6 years and >30 years, respectively, also did not reveal any infected frogs [18], and toad lungworms have not caused mortality in experimentally infected adult Green Treefrogs [54]. Broadly, then, our results are encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…One of these species (the Green Treefrog, Litoria caerulea ) shows no overt ill effects from the infections whereas the other (Magnificent Treefrog, L. splendida ) exhibits high levels of mortality [17]. Thus, an absence of records of the toad lungworm in Australian native frogs from surveys [18] might reflect either a lack of transmission, or high mortality of infected frogs. The cane toad invasion has already spread through large areas containing L. caerulea , and has now reached areas containing L. splendida .…”
Section: Introductionmentioning
confidence: 99%
“…Also, both laboratory and field studies showed that lungworm infection reduces the growth rates of adult toads by twofold (Kelehear et al 2011a). Field surveys of anuran parasites suggested that the toad's lungworm has not spread to any Australian frogs (Dubey and Shine 2008;Pizzatto et al 2012). Earlier studies on other bufonid-Rhabdias interactions also have reported detrimental effects of the parasite on growth, locomotor performance, and survival of the host (Goater and Ward 1992;Goater et al 1993;Moretti et al 2014).…”
Section: Introductionmentioning
confidence: 89%